Hubungan Cognitive Dissonance dengan Perilaku Konsumtif Pada Mahasiswa - Utami, Fitria Wahyu; Sudrajat, Ajat; Putri, Riska Mayasta; Puspitawati, Nadila (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study is intended to determine the effect of the relationship between Cognitive Dissonance and Consumptive Behavior in College Students. Hypothesis development H0: There is no significant influence between Cognitive Dissonance and Consumptive Behavior. H1 : There is a significant influence between Cognitive Dissonance and Consumptive Behavior. The population of the study were all students at Singaperbangsa University in Karawang. The number of samples in this study were 100 respondents with the sampling method used was a non-probability method with purposive sampling technique with certain considerations. Then hypothesis testing was carried out to determine the relationship between variables with the results of the Cognitive Dissonance Variable obtained a statistical t value of 3.097> 1.96 or p values of 0.002 <0.05, it was concluded that H1 was accepted, Cognitive Dissonance had a significant effect on Consumptive Behavior